Pengembangan Media Scratch Game Edukasi Berbasis Gaya Belajar untuk Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar - Ma'wa, Putri Fajri; Ratnaningrum, Ika (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to develop educational Scratch game media based on learning styles and determine its feasibility and effectiveness to improve student learning outcomes.Method – This research design is Research and Development (R&D) with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. Findings – This research was conducted with the development of educational Scratch game media based on learning styles that contain IPAS class V material about changes in the earth due to human activities. The novelty in this study is in the form of media development tailored to learning styles, media access without downloading applications, and selection of materials that are different from previous studies. The feasibility of educational Scratch game media was rated very feasible by media experts with a score of 92% and by material experts at 84%. The results of student responses on small-scale and large-scale trials amounted to 86.58% and from teacher responses of 95% which were in the very feasible category. The level of effectiveness of educational Scratch game media based on learning styles is considered quite effective with the results of the N-Gain percent test of 63% and the N-Gain value of 0.63 which shows the difference in learning outcomes at a moderate level. Research Implications – The results of the research conducted have implications for the development of educational Scratch game media based on learning styles that can be used as a reference for developing media according to student characteristics.